Dampak Eksploitasi Kerentanan Web terhadap Integritas Data: Tinjauan Kewajiban Etis dan Legalitas Developer - Muhamad Nazry Khoiry; Evy Nurmiati (Journal of Engineering and Applied Technology, 2026)
Web application security vulnerabilities, specifically SQL injection, pose a critical threat to data integrity, directly undermining the foundational security pillars of accuracy, completeness, and consistency. This study investigates the impact of such exploits through controlled black-box penetration testing on vulnerable prototypes, subsequently analyzing the findings against ethical engineering frameworks and Indonesian cyber law regulations. Empirical evidence demonstrates that inadequate security configurations lead to unauthorized data exfiltration and mass manipulation, which constitutes a severe breach of professional developer responsibilities. The research highlights that technical failures are inextricably linked to legal and ethical accountability, necessitating a transition from reactive patching to a proactive, security-by-design development paradigm. By mapping technical vulnerabilities to the governing legal statutes and professional ethics codes, this article establishes a mandate for developers to prioritize robust security architectures. The study underscores that strengthening digital resilience requires a cohesive integration of advanced technical defense mechanisms with strict adherence to national regulatory frameworks to ensure long-term data security and institutional accountability in the digital era.